Speak for yourself : talk to impress, influence and make an impact - Key, Harry (Pearson, 2014)
If you think that talking is easy, think again! Why? Because, whether at a meeting at work or a dinner party at home, what you're saying and how you're saying it matters. It can open doors - or close them; it can make you friends - or lose them; it can get you noticed - or forgotten. Wish you were a raconteur? Or a brilliant public speaker? Maybe you just want to be more confident, clever, persuasive or provocative in everyday conversations. Whatever you want, with some simple, fun and effective techniques Speak for Yourself will help you master: Your voice - make an impact and be hea.